Cemara (Cegah Anemia Remaja): Membangun Generasi Remaja Sehat, Aktif dan Bebas Anemia Pada Siswa SMK Dharma Bakti Indonesia - Wulan Novika Ambarsari; Afrieani Deasy; Rudi Karmi; Ayu Apriyani; Putri Nabila; Riani Ayu Lestari (Jurnal Pengabdian Masyarakat Sabangka, 2026)
Adolescence is a critical period of rapid growth that requires adequate nutritional intake, particularly iron. Nevertheless, anemia remains a common nutritional problem among adolescents and can negatively affect concentration, academic achievement, productivity, and future reproductive health. Limited knowledge about its causes, consequences, and prevention contributes to its high prevalence. The community service program “CEMARA (Preventing Adolescent Anemia): Building Healthy, Active, and Anemia-Free Adolescents” aimed to improve students’ knowledge of anemia prevention. Using a one-group pretest-posttest design, the program involved 61 students from SMK Dharma Bakti Indonesia across various grades and study programs. Data were analyzed descriptively and with the Marginal Homogeneity test. Good knowledge increased from 14.8% to 77.0%, while poor knowledge decreased from 52.5% to 8.2%. The difference was statistically significant (p<0.05), indicating that e-booklet-based health education effectively improved adolescents’ knowledge and should be implemented continuously in schools nationwide.